A theory-informed systematic review to understand physical activity among women in Gulf Cooperation Council countries - Lujain A. Osabi; Joris van de Klundert; Sultana A. Alhurishi; J. M. Cramm (BMC, 2023)
Abstract Background This systematic review was conducted to identify health beliefs and modifying factors influencing physical (in) activity among adult women in Gulf Cooperation Council (GCC) countries (Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and the United Arab Emirates). Methods A comprehensive search of the Medline (Ovid), EMBASE, Cochrane Central, Web of Science, and Google Scholar databases was conducted to identify relevant articles published between 2009 and 2019. The quality of included studies was assessed using the Mixed Methods Appraisal Tool. Data collection and analysis based on the health belief model were performed to systematically examine the relationships of health beliefs and modifying factors to physical activity. Results The sample comprised 15 studies (Saudi Arabia, n = 6; Oman, n = 5; Qatar, n = 2; Kuwait, n = 2). Reported physical activity prevalences were low (nearly 0% to 50%) and depended on the location, subpopulation, and measurement instrument. Evidence for relationships of modifying factors and health beliefs to physical activity was scarce and sometimes inconclusive. Among modifying factors, middle age and employment were associated positively with physical activity; marital status, educational level, income, and body mass index were not associated. Regarding health beliefs, the only conclusive evidence reported was that a lack of time was not associated significantly with physical activity in a population of men and women. Women reported a lack of social support and lack of skills significantly more frequently than men; these factors may explain the gender difference in physical activity prevalence. Differences in the reporting of fear of injury and lack of willpower were not significant. Conclusions Robust qualitative and quantitative research on the contributions of health beliefs and modifying factors to the low prevalence of physical activity among women in GCC countries is urgently needed. Current evidence indicates that unemployed women, women aged < 25 years, and elderly women are less likely to be physically active. Women in this population are more likely than men to believe that a lack social support and skills affects their physical activity. Many known factors and health beliefs appear to be unrelated to physical activity among adult women in GCC countries.